The Effectiveness Of Learning Media In Enhanching Students’ Motivation To Learn - Anggi Bela Komara; Aaz Fauzi Wahid; Nur Saffana Saskia Kirana; Adinda Cahyani; Akbar Firmansyah; Eko Ribawati (Gudang Jurnal Multidisiplin Ilmu, 2024)
This research investigates the influence of classroom environment and psychological factors on English learning motivation at SMP Negeri 14 Kota Serang. A conducive classroom environment is deemed crucial in shaping students' attitudes towards using English, yet it often faces challenges such as different pronunciation from standard English and social stigma related to using a foreign language outside of classroom contexts. A qualitative research method employing in-depth interviews was used to explore students' and teachers' perceptions regarding these issues. The findings reveal that many students feel insecure and embarrassed when using English, mainly due to their different accents and negative perceptions of their surroundings. However, teacher support and an inclusive classroom atmosphere can alleviate these barriers and enhance students' motivation to learn English. These findings underscore the importance of teaching approaches that accommodate student diversity and build their confidence in using a foreign language.